A protocol for generation and live-cell imaging analysis of primary cilia reporter cell lines - Binó, Lucia; Mikulenková, Erika; Štepánek, Luděk; Bernatík, Ondřej; Vysloužil, David; Pejšková, Petra; Gorilák, Peter; Huranová, Martina; Varga, Vladimír; Čajánek, Lukáš (STAR protocols, 2022)
Primary cilia are hair-like sensory organelles protruding from the surface of most human cells. As cilia are dynamic, several aspects of their biology can only be revealed by real-time analysis in living cells. Here we describe the generation of primary cilia reporter cell lines. Furthermore, we provide a detailed protocol of how to use the reporter cell lines for live-cell imaging microscopy analysis of primary cilia to study their growth as well as intraciliary transport. For complete details on the use and execution of this protocol, please refer to Bernatik et al. (2020) and Pejskova et al. (2020).
Keywords: Cell culture; buněčné linie; cilie; Cell Biology; Humans; Microscopy; Cell Line; Molecular Biology; lidé; mikroskopie; Cilia; počítačové zpracování obrazu; Image Processing, Computer-Assisted